Evaluating the efficacy of probiotics in atopic dermatitis on the background of food allergy in children - S.L. Nyankovskyy; О.S. Nyankovska; M.I. Horodylovska; Ya.V. Tomkiv; H.Z. Vivcharivska; V.D. Shaidych; O.M. Horayska; L.V. Zastavna; A.V. Vozniak; H.M. Trotskyy; A.Ye. Lisnyy; Z.V. Tomkiv (Zaslavsky O.Yu., 2019)
Background. According to the European Academy of Allergy and Clinical Immunology, about 17.3 % of European population has food allergies throughout life. At the same time, an increased concentration of specific immunoglobulins E to food is determined in 12.2 % of children and adolescents and in 4.1 % of adults. Atopic dermatitis is a common chronic inflammatory skin disease affecting up to 20 % of children and 10 % of adults in developed countries. The purpose of our research was to study the efficacy of probiotics Lactiale for children and Lactiale baby in children with atopic dermatitis and food allergy. Materials and methods. We observed 97 children aged from 6 months to 9 years with atopic dermatitis and food allergy. They were divided into 2 groups. The main group consisted of 59 children who received probiotics Lactiale for children or Lactiale baby for 3 months. The control group consisted of 38 children who did not receive probiotic. They were given only general recommendations. Results. Food allergy and atopic dermatitis are one of the actual problems in modern pediatrics, because they occupy one of the dominant positions in the structure of young children diseases. It was found that the food allergy and atopic dermatitis were more severe in children of the main group, the symptoms of the disorder of the general condition and the indicators of scatological and bacteriological feces studies were significantly worse than in the children of the control group. But at the end of the study, there was a significantly better positive dynamics in the group, which additionally received probiotics Lactiale for children or Lactiale baby that testifies to its efficacy and the possibility of recommending its inclusion to the treatment regimens in allergic diseases, food allergies and atopic dermatitis in particular.